Response of the low‐latitude D region ionosphere to extreme space weather event of 14–16 December 2006. Issue 1 (30th January 2015) - Kumar, Sushil; Kumar, Abhikesh; Menk, Frederick; Maurya, Ajeet K.; Singh, Rajesh; Veenadhari, B.
Abstract The response of the D region low‐latitude ionosphere has been examined for extreme space weather event of 14–16 December 2006 associated with a X1.5 solar flare and an intense geomagnetic storm (Dst = −146 nT) using VLF signals from Northwest Cape, Australia (NWC) (19.8 kHz) and Lualualei, Hawaii (callsign NPM) (21.4 kHz) transmitters monitored at Suva (Geographic Coordinates, 18.10°S, 178.40°E), Fiji. Modeling of flare associated amplitude and phase enhancements of NWC (3.6 dB, 223°) and NPM (5 dB, 153°) using Long‐Wave Propagation Capability code shows reduction in the D region reflection height (H′) by 11.1 km and 9.4 km, and enhancement in ionization gradients described by increases in the exponential sharpness factor (β) by 0.122 and 0.126 km−1, for the NWC and NPM paths, respectively. During the storm the daytime signal strengths of the NWC and NPM signals were reduced by 3.2 dB on 15 and 16 December (for about 46 h) and recovered by 17 December. Modeling for the NWC path shows that storm time values of H′ and β were reduced by 1.2 km and 0.06 km−1, respectively. Morlet wavelet analysis of signal amplitudes shows no clearly strong signatures of gravity wave propagation to low latitudes during the main and recovery phases. The reduction in VLF signal strength is due to increased signal attenuation and absorption by the Earth‐ionosphere waveguide due to storm‐induced D region ionization changes and hence changes in D region parameters. The long duration of the storm effect results from the slow diffusion of changed composition/ionization at D region altitudes compared with higher altitudes in the ionosphere.